2013
DOI: 10.1186/2193-1801-2-339
|View full text |Cite
|
Sign up to set email alerts
|

Use of in-vitro experimental results to model in-situ experiments: bio-denitrification under geological disposal conditions

Abstract: Some of the low level radioactive wastes from reprocessing of spent nuclear fuels contain nitrates. Nitrates can be present in the form of soluble salts and can be reduced by various reactions. Among them, reduction by metal compounds and microorganisms seems to be important in the underground repository. Reduction by microorganism is more important in near field area than inside the repository because high pH and extremely high salt concentration would prevent microorganism activities. In the near field, pH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It should be noted that the low denitrification rates remain significant considering the several thousand years of life of a nuclear waste repository. Other studies carried out in a comparable context showed that microbial communities or pure strains such as Pseudomonas stutzeri could reduce millimolar nitrate concentrations with denitrification rates up to 0.8 mM h À1 (Spain and Krumholz, 2011;Masuda et al, 2013;Bertron et al, 2013a). These studies were carried out in a pH range of 6e8 and with a rich culture medium.…”
Section: Bacterial Growth and Kinetics Of Denitrificationmentioning
confidence: 97%
“…It should be noted that the low denitrification rates remain significant considering the several thousand years of life of a nuclear waste repository. Other studies carried out in a comparable context showed that microbial communities or pure strains such as Pseudomonas stutzeri could reduce millimolar nitrate concentrations with denitrification rates up to 0.8 mM h À1 (Spain and Krumholz, 2011;Masuda et al, 2013;Bertron et al, 2013a). These studies were carried out in a pH range of 6e8 and with a rich culture medium.…”
Section: Bacterial Growth and Kinetics Of Denitrificationmentioning
confidence: 97%